UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL RME (REALISTIC MATHEMATICS EDUCATION) SISWA KELAS IX A SMP NEGERI 04 BUMIAYU SEMERTER 1 TAHUN PELAJARAN 2013/2014 - Sulastri Sulastri; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
Realistic mathematics education is one model to improve student’s motivation in learning and students' achievement. This research is Classroom Action Research (CAR). The subject of the research is nine grade students of Junior high school Bumiayu. It is conducted in two cycles, each cycles consists of planning, acting, observing and reflecting. The data revealed from observation, questionnaire, test and documentation. The result of the research was there are increasing student motivation and students' achievement. This forum can be teachers' reflection to be much better in mathematic teaching and learning.